Innovation Capital Efficiency as a Component of Intellectual Capital: Evidence from the Indian Food Manufacturing Sector (International Journal of Food and Nutritional Sciences, 2022)
This research examines the effect of innovation capital, an important element of intellectual capital, on the financial performance of Indian food processing firms between the years 2019–2023. Using secondary data obtained from the PROWESS database, innovation capital was quantified using the Pulic VAIC method. The research used Pooled OLS regression to examine the impact of innovation capital efficiency on firm performance, as captured by Return on Assets (ROA), while controlling for firm size, leverage, firm age, and R&D intensity. The findings illustrate that innovation capital positively and statistically affects firm performance, highlighting the importance of intangible assets in the competitiveness and profitability of food manufacturing companies. The implications suggest the necessity for corporate managers to give a higher priority to investing in innovation and for policymakers to create a pro-R&D environment. Implications of limitations in the current study and research opportunities are also considered, and more extensive and deeper investigations of the impact of intellectual capital on the success of a firm are underscored.